EFFECTIVENESS WASTE WATER OF RICE INOCULANT ON JASMINE (Jasminum sambac) - Elfarisna Elfarisna; Rita Tri Puspitasari; Yati Suryati; Nosa Tirtajaya Pradana (Jurnal AGROSAINS dan TEKNOLOGI, 2016)
Waste water of rice is one of the waste that can be used as a useful fertilizer for plant growth. It is potentially useful because much availability and easy in  processing. The study aims to know the effectiveness of waste water of rice  inoculant as organic fertilizer on jasmine. The study was conducted from February to August 2015 in the experimental field of the Faculty of Agriculture, University of Muhammadiyah Jakarta. Materials used are Jasminum sambac generative phase, polybag, cow manure, rice husk, waste water of  rice, brown sugar, isolates MOL, Hyponex (25-5-20), Gandasil B, and vitamin B6. Research using randomized complete block design with treatments: M1= inoculant I (three bacteria and two yeast), M2= inoculant II (two bacteria and two yeast), M3= 50% (inoculant I + inorganic fertilizer), M4= 50% (inoculant II + inorganic fertilizer), and M5= 100 % inorganic fertilizer, with five replication. Fertilization were done 2 times a week with a dose of 50 mL plant-1. Inorganic fertilizer (control) is givenbythe sequence is Hyponex - Gandasil - vitamin B6. The results showed not significantly different between the fertilizer  waste water of rice inoculant than inorganic fertilizers for all parameters. Inoculant tends to give better than others.